Self-confidence level among students of Raparin University who have undergone cosmetic surgery (Raparin Journal of Humanities (RJH), 2023)
The problem of the research, when the level of (Self-confidence) is High, the   individual enjoys good mental and somatic health, but, when the level of Self-confidence is less, it may lead to a lack of logical analysis or challenge and control and create difficulties in decision-making as a result of weak confidence in the information obtained in a negative way on the individual's body and facial image. The importance of self-confidence as a personality variable plays an influential role in the individual and Society in the face of the challenges in individual life that continue to be optimistic and positive. The aimes of this study are to determine the level of self-confidence among university students who have undergone cosmetic surgery. Determining the differences in self-confidence levels among university student who have undergone cosmetic surgery according to gender (male-female) and specialty (science-humanities). The researchers took the descriptive method approach. The research community consisted of 60 students of Raparin University who underwent cosmetic surgery. The sample was randomly selected, including 50 students, including 17 males and 33 females in University of Raparin for the academic year (2019-2020) in the morning. The researchers prepared a scale consisting of (20) item to measure the level of self-confidence among university students who have undergone cosmetic surgery. The results showed   statistically levels of high in Self-Confidence. There was no statistically significant difference in self-confidence by gender and specialty, but the specialty variable in the sample itself showed differences in favor of the humanities